Plan de negocio para la creación de un bróker dedicado a la exportación de barras de chocolate elaboradas por pymes ecuatorianas hacia Estados Unidos - Ayala Morante, Andrea Valeria (2016)
In Ecuador there is not a broker specialized in chocolates business, although the demand of exporting the best chocolate in the whole world, which is the Ecuadorian; overtaking the traditional countries such as Switzerland, Madagascar, Germany (Embassy of Ecuador, n.d). The SMEs need assistance to get to know a new market that will bring positive rewards in the countrys economy. The SMEs have a premium product which is required in the US market, which record in 2013 imports increased 9.3% (Pro Ecuador, 2013). According to the external analysis conducted we found that customers seek advice, drivability and overseas market. Companies currently offer similar services do not give enough advice and positioner not care about small traders in the international market, resulting in large financial losses for customers and also losing ground abroad. This is how the concept of Export Guide and the business opportunity of a broker dedicated export of chocolate bars made by Ecuadorian SMEs begins. Offering a comprehensive service that is responsible for meeting the needs of an international market focusing them to customers. The target market will be SMEs that are in the city of Quito chocolate producers